Primary Sclerosing Cholangitis : Current Understanding, Management, and Future Developments - Forman, Lisa M. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a state-of-the art review of primary sclerosing cholangitis (PSC). The volume focuses on new data about the risk factors for PSC, its natural history of the disease, and the epidemiology and genetics of PSC, while providing a comprehensive overview on current and future therapies for PSC, management of cholangiocarcinoma, and other hepatobiliary malignancies. It also touches upon up-to-date surgical and endoscopic management, including liver transplantation-both deceased donor and living related liver transplantation. Written by experts in the field, Primary Sclerosing Cholangitis: Current Understanding, Management, and Future Developments is a valuable resource for clinicians, surgeons and researchers with an interest in biliary liver disease, inflammatory bowel disease, and liver transplantation.
Keywords: Medicine.; Gastroenterology.; Hepatology.; elektronické knihy; electronic books